Do Referral Reward Programs Enhance Customer Loyalty? – Results of a Propensity Score Matching Study - Garnefeld, I; Helm, S; Eggert, A; Tax, S (Proceedings of the 2010 AMA Summer Marketing Educators' Conference)

Disentangling the Revenue and Cost Implications of the Service Transition: A Latent Growth Analysis - Eggert, A; Hogreve, J; Ulaga, W; Münkhoff, E (Proceedings of the 2nd ISBM Workshop at Harvard Business School)

Corporate Reputation and Customers’ Value Perceptions: A Dynamic Analysis - Frick, B; Eggert, A; Hogreve, J (Proceedings of the 39th EMAC Conference)

Industrial Services, Product Innovations, and Firm Profitability – A Longitudinal Analysis - Eggert, A; Hogreve, J; Ulaga, W; Münkhoff, E (Proceedings of the Frontiers Pre-Conference on Service and Solution Innovation)

Exploring the Effects of Referral Reward Programs on Satisfied and Dissatisfied Customers - Garnefeld, I; Münkhoff, E; Hogreve, J; Eggert, A (Proceedings of the 2010 AMA Winter Marketing Educators' Conference)

Correlation-induced single-flux-quantum penetration in quantum rings - Giesbers, A. J. M.; Zeitler, U.; Katsnelson, M. I.; Reuter, Dirk; Wieck, A. D.; Biasiol, G.; Sorba, L.; Maan, J. C. (Nature Physics)

Observation of orientation- andk-dependent Zeeman spin-splitting in hole quantum wires on (100)-oriented AlGaAs/GaAs heterostructures - Chen, J C H; Klochan, O; Micolich, A P; Hamilton, A R; Martin, T P; Ho, L H; Zülicke, U; Reuter, Dirk; Wieck, A D (New Journal of Physics)

Electronic structure of self-assembled InGaAs/GaAs quantum rings studied by capacitance-voltage spectroscopy - Lei, W.; Notthoff, C.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Quantized Magnetic Confinement in Quantum Wires - Tarasov, A.; Hugger, S.; Xu, Hengyi; Cerchez, M.; Heinzel, T.; Zozoulenko, I. V.; Gasser-Szerer, U.; Reuter, Dirk; Wieck, A. D. (Physical Review Letters)

Spin dynamics of electrons and holes inInGaAs/GaAsquantum wells at millikelvin temperatures - Fokina, L. V.; Yugova, I. A.; Yakovlev, D. R.; Glazov, M. M.; Akimov, I. A.; Greilich, A.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Spin Noise of Electrons and Holes in Self-Assembled Quantum Dots - Crooker, S. A.; Brandt, J.; Sandfort, C.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review Letters)

Electronic structure of self-assembled InGaAs/GaAs quantum rings studied by capacitance-voltage spectroscopy - Lei, W.; Notthoff, C.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Control of the transmission phase in an asymmetric four-terminal Aharonov-Bohm interferometer - Buchholz, Sven S.; Fischer, Saskia F.; Kunze, Ulrich; Bell, Matthew; Reuter, Dirk; Wieck, Andreas D. (Physical Review B)

Nanostructures in p-GaAs with improved tunability - Csontos, M.; Komijani, Y.; Shorubalko, I.; Ensslin, K.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Full-wave rectification based upon hot-electron thermopower - Wiemann, M.; Wieser, U.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Enhanced Sequential Carrier Capture into Individual Quantum Dots and Quantum Posts Controlled by Surface Acoustic Waves - Völk, Stefan; Schülein, Florian J. R.; Knall, Florian; Reuter, Dirk; Wieck, Andreas D.; Truong, Tuan A.; Kim, Hyochul; Petroff, Pierre M.; Wixforth, Achim; Krenner, Hubert J. (Nano Letters)

Epitaxial growth and interfacial magnetism of spin aligner for remanent spin injection: [Fe/Tb]n/Fe/MgO/GaAs-light emitting diode as a prototype system - Schuster, E.; Brand, R. A.; Stromberg, F.; Ludwig, A.; Reuter, Dirk; Wieck, A. D.; Hövel, S.; Gerhardt, N. C.; Hofmann, M. R.; Wende, H.; Keune, W. (Journal of Applied Physics)

Evidence for localization and 0.7 anomaly in hole quantum point contacts - Komijani, Y.; Csontos, M.; Shorubalko, I.; Ihn, T.; Ensslin, K.; Meir, Y.; Reuter, Dirk; Wieck, A. D. (EPL (Europhysics Letters))

A two-dimensional electron gas as a sensitive detector to observe the charge carrier dynamics of self-assembled QDs - Marquardt, Bastian; Geller, Martin; Lorke, Axel; Reuter, Dirk; Wieck, Andreas D. (Physica E: Low-dimensional Systems and Nanostructures)

“Artificial Atoms” in Magnetic Fields: Wave-Function Shaping and Phase-Sensitive Tunneling - Lei, Wen; Notthoff, Christian; Peng, Jie; Reuter, Dirk; Wieck, Andreas; Bester, Gabriel; Lorke, Axel (Physical Review Letters)

Phase shifts and phaseπjumps in four-terminal waveguide Aharonov-Bohm interferometers - Kreisbeck, Christoph; Kramer, Tobias; Buchholz, Sven S.; Fischer, Saskia F.; Kunze, Ulrich; Reuter, Dirk; Wieck, Andreas D. (Physical Review B)

An intentionally positioned (In,Ga)As quantum dot in a micron sized light emitting diode - Mehta, M.; Reuter, Dirk; Wieck, A. D.; Michaelis de Vasconcellos, S.; Zrenner, A.; Meier, C. (Applied Physics Letters)

Capacitance-voltage spectroscopy on InAs quantum dot valence band states in tilted magnetic fields - Reuter, Dirk; Roescu, R; Zeitler, U; Maan, J C; Wieck, A D (Journal of Physics: Conference Series)

Optical probing of spin dynamics of two-dimensional and bulk electrons in a GaAs/AlGaAs heterojunction system - Rizo, P J; Pugzlys, A; Slachter, A; Denega, S Z; Reuter, Dirk; Wieck, A D; van Loosdrecht, P H M; van der Wal, C H (New Journal of Physics)

Holistic Model-Based Testing for Business Information Systems - Mlynarski, Michael (Proceedings of 3rd International Conference on Software Testing, Verification and Validation)

A Generic Meta-Model-based Approach for Specifying Framework Functionality and Usage - Christ, Fabian; Bals, Jan-Christopher; Engels, Gregor; Gerth, Christian; Luckey, Markus (Proceedings of the 48th International Conference on Objects, Models, Components and Patterns (TOOLS'10), Málaga (Spain))

Graph Transformations and Model-Driven Engineering: The Merits of Manfred Nagl - Engels, Gregor; Lewerentz, Claus; Schäfer, Wilhelm; Schürr, Andy; Westfechtel, Bernhard (Graph Transformations and Model-Driven Engineering)

Knowledge Transfer in Global Software Development - Leveraging Acceptance Test Case Specifications - Engels, Gregor; Salger, Frank (In Proceedings of the ACM/IEEE 32nd International Conference on Software Engineering (ICSE), New Ideas and Emergent Results program, May 2010, Cape Town (South Africa))

Proceedings 12. Workshop Software-Reengineering (WSR) & 2. Workshop Design for Future 2010 (DFF) - Gimnich, Rainer; Kaiser, Uwe; Momm, Christof; Quante, Jochen; Riediger, Volker; Sauer, Stefan; Trifu, Mircea; Winter, Andreas

Precise Detection of Conflicting Change Operations using Process Model Terms - Gerth, Christian; Küster, Jochen; Luckey, Markus; Engels, Gregor (Proceedings of the ACM/IEEE 13th International Conference on Model Driven Engineering Languages and Systems (MODELS'10))
Version management of process models requires that changes can be resolved by applying change operations. Conflict detection is an important part of version management and the minimization of the number of detected conflicts also reduces the overhead when resolving changes. As not every syntactic conflict leads to a conflict when taking into account model semantics, a computation of conflicts solely on the syntax leads to an unnecessary high number of conflicts. In this paper, we introduce the notion of syntactic and semantic conflicts for change operations of process models. We provide a method how to efficiently compute conflicts, using a term formalization of process models. Using this approach, we can significantly reduce the number of overall conflicts and thereby reduce the amount of work for the user when resolving conflicts.

Detection of Semantically Equivalent Fragments for Business Process Model Change Management - Gerth, Christian; Luckey, Markus; Küster, Jochen; Engels, Gregor (Proceedings of the IEEE 7th International Conference on Services Computing (SCC'10))

Enriching RUP with key success factors for large-scale custom software development projects - Heinemann, Marianne; Duwe, Bettina; Engels, Gregor (Software & Systems Engineering Essentials (SEE) 2010)

Auswahl projektspezifischer Vorgehensstrategien - Heinemann, Marianne; Engels, Gregor (Integration von Vorgehensmodellen und Projektmanagement)

Computergestützte traumatherapeutische Behandlungsmöglichkeiten bei Verkehrsunfallopfern von Kinder und Jugendlichen - Huck, Wilfried; Alakbarov, Alexej; Domik, Gitta; Radkowski, Rafael; Tölke, Roswitha; Mikus, Ann-Cathrin; Geisen, Silke (12. Jahrestagung der Deutschsprachigen Gesellschaft für Psychotraumatologie (DeGPT))

Dynamic Computation of Change Operations in Version Management of Business Process Models - Küster, Jochen; Gerth, Christian; Engels, Gregor (Proceedings of the 6th European Conference on Modelling Foundations and Applications (ECMFA'10))
Version management of business process models requires that changes can be resolved by applying change operations. In order to give a user maximal freedom concerning the application order of change operations, position parameters of change operations must be computed dynamically during change resolution. In such an approach, change operations with computed position parameters must be applicable on the model and dependencies and conflicts of change operations must be taken into account because otherwise invalid models can be constructed. In this paper, we study the concept of partially specified change operations where parameters are computed dynamically. We provide a formalization for partially specified change operations using graph transformation and provide a concept for their applicability. Based on this, we study potential dependencies and conflicts of change operations and show how these can be taken into account within change resolution. Using our approach, a user can resolve changes of business process models without being unnecessarily restricted to a certain order.

A Meta-Method for Defining Software Engineering Methods - Engels, Gregor; Sauer, Stefan (Graph Transformations and Model-Driven Engineering)

Erweiterung des TPI-Modells zur Reifegradbewertung unter Berücksichtigung von projekteigenen Anforderungen - Sancar, Yavuz; Schumacher, Claudia (Proceedings of the Conference on Software & Systems Engineering Essentials 2010 (SEE 2010), Köln (Germany))

Assessments in Global Software Development: A Tailorable Framework for Industrial Projects - Salger, Frank; Engels, Gregor; Hofmann, Alexander (Proceedings ACM/IEEE 32nd International Conference on Software Engineering, Software Engineering in Practice Track, Cape Town, South Africa (ICSE'10))

SheetDiff: A Tool for Identifying Changes in Spreadsheets - Chambers, Chris; Erwig, Martin; Luckey, Markus (Proceedings of the 26th IEEE Symposium on Visual Languages and Human-Centric Computing 2010 (VL/HCC 2010))

Model-driven Development of Advanced User Interfaces - Van den Bergh, Jan; Meixner, Gerrit; Breiner, Kai; Pleuß, Andreas; Sauer, Stefan; Hussmann, Heinrich (Proc. 28th International Conference on Human Factors in Computing Systems (CHI 2010))

Transfer of Testing Research from University to Industry: An Experience Report - Güldali, Baris; Sauer, Stefan (online Proc. of International TestIstanbul Conference 2010 (URL: www.testistanbul.org/presentations.html))
Software Quality Lab (s-lab) is an open multi-private-public partnership institute for knowledge and technology transfer. In s-lab, partners from industrial software development closely cooperate with research groups of the University of Paderborn. Together with partners from industry, s-lab develops and evaluates constructive and analytical methods and tools of software engineering for obtaining high-quality software. Testing plays an important role in analytical quality assurance within s-lab’s activities. Thereby our main focus lies on the development of testing methods, test automation tools and test management concepts for the individual needs of the industrial partners. Because of the different requirements of the university and the industry; the cooperation involves some challenges, e.g. defining projects aiming at the commercial interests of the industry and addressing interesting research questions. In this paper, we give an overview of testing activities in s-lab and address targets and challenges of the cooperative work between industry and university. We also summarize the lessons learned during the numerous testing projects especially in the domain of business information systems.

Verteiltes Testen heterogener Systemlandschaften - von der Maßen, Thomas; Wübbeke, Andreas (Proceedings of Software Engineering 2010 (SE2010))

Cooperative feedback to improve capacity and error rate in multiuser diversity systems - an OFDM case study - Valentin, Stefan; Karl, Holger (European Transactions on Telecommunications)

Expected interference in wireless networks with geometric path loss: a closed-form approximation - S. Lichte, Hermann; Valentin, Stefan; Karl, Holger (IEEE Communications Letters)

Automated Development of Cooperative MAC Protocols - A Compiler-Assisted Approach - Simon Lichte, Hermann; Valentin, Stefan; Karl, Holger (Mobile Networks and Applications)

Concept and Prototype for a Real-Time Enabled Publish/Subscribe System - Andree, Matthias; Gebel, Alexander; Karl, Holger (10th IEEE International Conference on Computer and Information Technology, CIT 2010, Bradford, West Yorkshire, UK, June 29-July 1, 2010)

Risk Aware Overbooking for Commercial Grids - Birkenheuer, Georg; Brinkmann, Andre; Karl, Holger (Job Scheduling Strategies for Parallel Processing - 15th International Workshop, JSSPP 2010, Atlanta, GA, USA, April 23, 2010, Revised Selected Papers)

Fading-resistant low-latency broadcasts in wireless multihop networks: the probabilistic cooperation diversity approach - S. Lichte, Hermann; Frey, Hannes; Karl, Holger (Proceedings of the 11th ACM Interational Symposium on Mobile Ad Hoc Networking and Computing, MobiHoc 2010, Chicago, IL, USA, September 20-24, 2010)

FIT: Future Internet Toolbox - Biermann, Thorsten; Dannewitz, Christian; Karl, Holger (Testbeds and Research Infrastructures. Development of Networks and Communities - 6th International ICST Conference, TridentCom 2010, Berlin, Germany, May 18-20, 2010, Revised Selected Papers)

Prototyping with the Future Internet Toolbox - Dannewitz, Christian; Biermann, Thorsten; Dräxler, Martin; Beister, Frederic; Karl, Holger (Testbeds and Research Infrastructures. Development of Networks and Communities - 6th International ICST Conference, TridentCom 2010, Berlin, Germany, May 18-20, 2010, Revised Selected Papers)